Performance Evaluation of Bigeye Bycatch Reduction Device in the Seas off Cochin, India - Sabu, S; Gibinkumar, T R; Pravin, p; Boopendranath, M R (Fishery Technology, 2025)
Trawling is one of the most non-selective methods of fish capture. Incidental bycatch and discards are serious issues related to trawling, leading to the depletion of the resources and biodiversity. Devices used to reduce bycatch from fishing gear are known as Bycatch Reduction Devices (BRDs). Bigeye BRD consists of a horizontal slit in the upper part of the codend or hind belly, where the opening is maintained by means of floats and sinkers. Comparative performance evaluation of Bigeye BRDs fixed at two different positions on shrimp trawl codends was conducted off Cochin, during 2006-2007. Bigeye BRDs positioned at (i) 0.5 m from the leading edge of the codend (Bigeye-0.5) and (ii) 1.5 m from the distal end of codend (Bigeye-1.5) were constructed on 20 mm diamond mesh codends. Comparative field trials with Bigeye-0.5 and Bigeye-1.5 BRDs in the seas off Cochin have given bycatch exclusion rates ranging from 8 to 11% and shrimp loss ranging from 1 to 2%. Among the two Bigeye BRDs evaluated, Bigeye-1.5 performed comparatively better in terms of bycatch exclusion. Bigeye BRD is simple in design, easy to fabricate and incurs low cost. Considering these advantages, Bigeye BRD positioned at 1.5 m from the distal end of the codend has potential for adoption by the shrimp trawling industry in India to reduce finfish bycatch from shrimp trawls.